Multicenter study on differential human neutrophil antigen 2 expression and underlying molecular mechanisms - Flesch, Brigitte; Reil, Angelika; Nogués, Núria; Canals, Carme; Bugert, Peter; Schulze, Torsten; Huiskes, Elly; Porcelijn, Leendert; Höglund, Petter; Ratcliffe, Paul; Schönbacher, Marlies; Kerchrom, Hans; et al. (Transfusion medicine and hemotherapy, 2020)
Background: The human neutrophil antigen 2 (HNA-2), which is expressed on CD177, is undetectable in 3-5% of the normal population. Exposure of these HNA-2null individuals to HNA-2-positive cells can cause immunization and pro-duction of HNA-2 antibodies, which can induce immune neutropenia and transfusion-related acute lung injury. In HNA-2-positive individuals, neutrophils are divided into a CD177pos. and a CD177neg. subpopulation. The molecular background of HNA-2 deficiency and the bimodal expression pattern, however, are not completely decoded. Study Design: An international collaboration was conducted on the genetic analysis of HNA-2-phenotyped blood samples, including HNA-2-deficient individuals, mothers, and the respective children with neonatal immune neutropenia and regular blood donors. Results: From a total of 54 HNA-2null individuals, 43 were homozygous for the CD177*787A>T substitution. Six carried the CD177*c.1291G>A single nucleotide polymorphism. All HNA-2-positive samples with >40% CD177pos. neutrophils carried the *787A wild-type allele, whereas a lower rate of CD177pos. neutrophils was preferentially associated with *c.787AT heterozygosity. Interestingly, only the *c.787A allele sequence was detected in complementary DNA (cDNA) sequence analysis carried out on all *c.787AT heterozygous individuals. However, cDNA analysis after sorting of CD177pos. and CD177neg. neutrophil subsets from HNA-2-positive individuals showed identical sequences, which makes regulatory elements within the promoter unlikely to affect CD177 gene transcription in different CD177 neutrophil subsets. Conclusion: This comprehensive study clearly demonstrates the impact of single nucleotide polymorphisms on the expression of HNA-2 on the neutrophil surface but challenges the hypothesis of regulatory epigenetic effects being implicated in the bimodal CD177 expression pattern.